Physiological responses of soybean cultivars to potassium fertilization under different water regimes - Catuchi, Tiago Aranda; Guidorizzi, Fernando Vieira Costa; Guidorizi, Kezia Aparecida; Barbosa, Alexandrius de Moraes; Souza, Gustavo Maia (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the interference of potassium fertilization on the physiological parameters of soybean cultivars under different water regimes. The experiment was carried out in greenhouse at Presidente Prudente, SP, Brazil. The experimental design was a completely randomized block in a 2x2x3 factorial arrangement, with the soybean cultivars BR‑16 (tolerante ...) and Embrapa 48 (suscept...), water regimes with daily replacements of 100% (control) and 40% of the field capacity, and three levels of K supplementation (0, 90, and 180 mg dm-3). Relative water content, photosynthetic potential, and biomass yield were evaluated two weeks after the initiation of water restriction. Plants grown under water restriction had their photosynthetic potential reevaluated after 12 h of rehydration. Under water restriction conditions, potassium fertilization did not significantly affect the assessed growth and physiological parameters. Supplementation with potassium promoted a better efficiency of the physiological parameters, in water deficit control, in both cultivars, and the main variables influenced by the nutrient were: stomatal conductance, maximum rate of Rubisco carboxylation, and maximum CO2 assimilation. Potassium supplementation improves photosynthetic recovery of plants after rehydration, especially in the Embrapa 48 cultivar.